Ric-8 controls Drosophila neural progenitor asymmetric division by regulating heterotrimeric G proteins. - Wang, H.; Ng, K.H.; Qian, H.; Siderovski, D.P.; Chia, W.; Yu, F. (Nature Cell Biology, 2005)
Asymmetric division of Drosophila neuroblasts (NBs) and the Caenorhabditis elegans zygote uses polarity cues provided by the Par proteins, as well as heterotrimeric G-protein-signalling that is activated by a receptor-independent mechanism mediated by GoLoco/GPR motif proteins. Another key component of this non-canonical G-protein activation mechanism is a non-receptor guanine nucleotide-exchange factor (GEF) for Galpha, RIC-8, which has recently been characterized in C. elegans and in mammals. We show here that the Drosophila Ric-8 homologue is required for asymmetric division of both NBs and pl cells. Ric-8 is necessary for membrane targeting of Galphai, Pins and Gbeta13F, presumably by regulating multiple Galpha subunit(s). Ric-8 forms an in vivo complex with Galphai and interacts preferentially with GDP-Galphai, which is consistent with Ric-8 acting as a GEF for Galphai. Comparisons of the phenotypes of Galphai, Ric-8, Gbeta13Fsingle and Ric-8;Gbeta13F double loss-of-function mutants indicate that, in NBs, Ric-8 positively regulates Gai activity. In addition, Gbetagamma acts to restrict Galphai (and GoLoco proteins) to the apical cortex, where Galphai (and Pins) can mediate asymmetric spindle geometry.